TEACHER ROOM APPLICATIONS FROM LEARNING COMMUNICATIONS MANAGEMENT PERSPECTIVE - Dewi K Soedarsono (SEAN Institute, 2022)
This research aims to find out how to use the learning space features in teacher room applications from the perspective of learning communication management; The object of the research was class IX students of SMPN 8 Bandung, which is one of the favorite schools in the city of Bandung. The method in this research is descriptive survey; and field data obtained through question questionnaires and distributed to several students of SMPN 8 bandung, as a research sample. Based on the results of the research , the aspects of the learning space features include, Audio Visual Video; Animation Video and Material are included in the category of good where through the study room features students more easily understand the learning material; the conclusion in this study using the perspective of learning communication management, in order to provide an overview of the extent to which the content on the learning space features can be effectively understood by users.